The search for meaningful e-learning at Canadian universities: a multi-institutional research study - Salyers, Vince; Carter, Lorraine; Carter, Alanna; Myers, Sue; Barrett, Penelope (My University, 2014)
While e-learning is now characterized by a past and trends within that past, there continues to be uncertainty about how e-learning is defined and conceptualized, whether or not we like e-learning, and whether or not it is as meaningful to us as face to face learning. The purpose of this study was to document the e-learning perceptions of students at three Canadian post-secondary institutions. Key components of e-learning courses including ease of navigation, course design, resource availability, and adequacy of e-learning supports and their impact on the student learning experience were also evaluated. Based on a survey of students (n = 1,377) as well as their participation in focus groups, the following are presented as important findings: the majority of students studying in e-learning courses at the three institutions represented in the study were women; ease of navigation, course design, and previous experience with e-learning consistently demonstrated a statistically significant predictive capacity for positive e-learning experiences; and students expressed less preference for e-learning instructional strategies than their faculty. Study findings hold implications for e-learning faculty, instructional designers, and administrators at institutions of higher education in Canada and elsewhere where e-learning is part of the institutional mandate. Additionally, further research into student perceptions of and experiences with e-learning is recommended.
Keywords: e-learning; mixed methods; navigation; design; infrastructure support; flexible learning